Avaliação da qualidade microbiológica de um composto produzido a partir de resíduos animais e vegetais - Cancelado, Sonia Villamizar [UNESP] (2014)
Daily and outbreaks mortality composting have been identified as the best method for final disposal of carcasses, but the potential risk of pathogens transmission seriously limits its use. In this study we assessed the microbiological quality and biosafety of a compost produced in experimental unit composting daily mortality at the university in the state of Sao Paulo, Brazil. Mature compost sample was evaluated to determine the presence of pathogenic bacteria E. coli (STEC) E. coli (EPEC) and E. coli (EHEC) using molecular techniques, the presence and counting of coliforms and Salmonella sp. and several soilborne phytopathogenic fungi was also estimated, the evaluation was conducted using selective and differential microbiological culture media. The presence of STEC, EPEC, Salmonella and phytopathogenic fungi were negative. Coliform levels were 1160 UFC/kg. The results show that daily mortality composting method is effective to reduce pathogenic microorganisms, but so the product can be applied on crops or plants such as vegetables that are for direct human consumption, additional tests must be performed to assess the presence of viral pathogens such as viruses avian influenza and Newcastle, endospores forming bacteria like Bacillus anthracis, should not be included dead animals by neurological diseases confirmed or probable